MUCOPOLYSACCHARIDOSIS TYPE II - N.D. Vashakmadze; L.S. Namazova-Baranova; A.K. Gevorkyan; L.M. Kuzenkova; A.D. Khristochevskiy; L.M. Vysotskaya; A.S. Dadashev (Педиатрическая фармакология, 2011)
Article is devoted to one of the orphan diseases — mucopolysaccharidosis (MPS), which is the result of any lysosomal enzyme deficiency (which determines the type of illness). The most common is the MPS type II (Hunter syndrome), developing as a result of deficiency of the enzyme alpha-L-iduronosulphatsulphataze. The authors are observing the largest group of children with this pathology in the Russian population — 40 patients. On the example of their own clinical cases the only existing on the date the pathogenetic treatment is provided — replacement therapy with idursulphase that significantly improves the disease prognosis.Key words: MPS, types, Hunter syndrome, clinical course, diagnosis, treatment, prognosis, children.